Metamathematics and Dogmatic Theology - Carnes, John R. (Scottish journal of theology, 1976)
Critics of the right wing of twentieth-century Protestant theology, most notably Neo-orthodoxy and more specifically the theology of Karl Barth, tend to be troubled by the central role given to what Barth calls the ‘science of dogmatics’. Their problem is twofold. (1) Dogmatics, at least in the Barthian conception of that science, appears to be exclusivist, accessible only to those who are already among the initiate, obscurantist, arrogant and even irrational. (2) Dogmatics is represented as the sole means of entry into theology: Barth uncompromisingly and aggressively rejects any other avenues. He is disdainful of philosophy, of philosophical theology, and even of ‘natural theology’ (see his treatment of Brunner in the early book, Natural Theology and his critique of Tillich in his very last book, Evangelical Theology).